Old T.I. : a book of pencil sketches and historical notes - O'Riley, M. J. (Matthew Joseph), 1941-; Wallace, I. B. (Cairns, Qld. : M.J. O'Riley and I.B. Wallace, 1977)
INCOMPLETE.
Keywords: Historic sites -- Queensland -- Thursday Island -- Pictorial works; Thursday Island (Qld.) -- Pictorial works; Thursday Island (Qld.) -- History -- Pictorial works; Waiben / Thursday Island (Qld TSI SC54-11)